2015
DOI: 10.1182/asheducation-2015.1.82
|View full text |Cite
|
Sign up to set email alerts
|

B-cell receptor pathway modulators in NHL

Abstract: With the recent success of the Bruton's tyrosine kinase (BTK) inhibitor, ibrutinib, and the phosphoinositide-3-kinase (PI3K) inhibitor, idelalisib, in the treatment of patients with relapsed or refractory non-Hodgkin's lymphoma (NHL), a number of new agents targeting the B-cell receptor (BCR) pathway are in clinical development. In addition, multiple trials combining these agents with conventional cytotoxic chemotherapy, immunomodulatory agents, monoclonal antibodies, or other kinase inhibitors are underway. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Early phase I and II clinical trials have shown beneficial effects, such as for ibrutinib in treating mantle cell lymphoma 34. However, acquired resistance and unexpected toxicities are common, and there is still much to learn in terms of how these drugs should be used.…”
Section: What New Treatments Can We Expect?mentioning
confidence: 99%
“…Early phase I and II clinical trials have shown beneficial effects, such as for ibrutinib in treating mantle cell lymphoma 34. However, acquired resistance and unexpected toxicities are common, and there is still much to learn in terms of how these drugs should be used.…”
Section: What New Treatments Can We Expect?mentioning
confidence: 99%
“…4). Indeed, recent advances in the understanding of disease biology, for instance, B-cell receptor modulators, including ibrutinib, an inhibitor of Bruton's tyrosine kinase, and idelalisib, an inhibitor of phosphatidylinositol 3-kinase for NHL, 28) and immune approaches, including checkpoint blockade with anti-PD-1 antibodies and adoptive cellular therapy with chimeric antigen receptor T cells for ALL and myeloma, 29) have been seen on the global level. This study confirm the same trends in Japan, and the availability of these new drugs and biological products is expected to improve in the near future, thereby providing new treatment options for existing patients, as well as advances in health care for the entire Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Through CD19 and adaptor protein-mediated recruitment of PI3K, BCR signals ultimately lead to the activation of the prosurvival signaling effectors AKT and NF-ï«Đ’ ( Fig. 2) (51). Various PI3K-AKT inhibitors are active in preclinical studies and preliminary trials, with idelalisib emerging as one of the frontrunners (Fig.…”
Section: Pi3k-akt-mtor Pathwaymentioning
confidence: 99%